PERSPEKTIF ORANG TUA TENTANG PROSES BELAJAR SISWA SEKOLAH DASAR DI MASA PANDEMI COVID 19 DI GAMPONG IE MASEN KAYEE ADANG KECAMATAN SYIAH KUALA KOTA BANDA ACEH - Arniati Sari; Riyan Mulfianda; Nanda Desreza (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The world is currently busy with the emergence of corona virus diseases (Covid 19). The government has made various efforts to limit activities, one of which is conducting an online learning process. The role of parents is important to accompany children during their studies. The purpose of this study was to determine the parents' perspective on the learning process of elementary school students during the covid 19 pandemic in Ie Masen Kayee Adang Village, Syiah Kuala District, Banda Aceh City in 2021. This type of research is descriptive observational, the research was carried out on June 14 to 19, 2021. The population in this study was all parents of elementary school age children living in Gampong Ie Masen Kayee Adang, Syiah Kuala District, Banda Aceh City, with sampling using proportional random sampling technique as many as 61 people. The results showed that most of the respondents' parental perspectives on the student learning process were in the less category as many as 35 respondents (57.4%), student learning process methods were in the good category as many as 31 respondents (50.8 %), student learning process are in the good category as many as 36 respondents (59%), student learning process are in the good category as many as 33 respondents (54.1%). it is hoped that this research can provide input for teachers in designing learning methods so that it is easy for students to understand when learning during the COVID-19 pandemic, so that it can make it easier for parents in learning process and can improve the learning achievement of children.